1987
DOI: 10.1200/jco.1987.5.4.622
|View full text |Cite
|
Sign up to set email alerts
|

Combined therapies for squamous-cell carcinoma of the esophagus, a Southwest Oncology Group Study (SWOG-8037).

Abstract: Conservative treatment of esophageal cancer with radiation therapy has afforded few long-term survivors. In order to improve outcome, patients with locoregional disease were treated using a combined modality approach. Patients were treated with chemotherapy consisting of a 96-hour continuous infusion of 5-fluorouracil (5-FU), 1,000 mg/m2/d, days 1 to 4 and days 29 to 32; cisplatin 75 mg/m2, day 1 and 29; and radiation 3,000 rad, days 1 to 19. In the absence of progressive disease, patients underwent esophagect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(69 citation statements)
references
References 5 publications
3
66
0
Order By: Relevance
“…The value of chemoradiotherapy for the treatment of unresectable oesophageal carcinoma remains controversial, and only a few clinical studies have been published since the 1980s (Leichman et al, 1984;Leichman et al, 1987;Poplin et al, 1987;Coia et al, 1991;Herskovic et al, 1992;Frorastiere et al, 1993;Poplin et al, 1994). Most patients in these studies had local -regional disease (UICC stage I or II).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of chemoradiotherapy for the treatment of unresectable oesophageal carcinoma remains controversial, and only a few clinical studies have been published since the 1980s (Leichman et al, 1984;Leichman et al, 1987;Poplin et al, 1987;Coia et al, 1991;Herskovic et al, 1992;Frorastiere et al, 1993;Poplin et al, 1994). Most patients in these studies had local -regional disease (UICC stage I or II).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported successful results with these modalities, either with or without surgery, against local -regional carcinoma (Leichman et al, 1984;Leichman et al, 1987;Poplin et al, 1987;Coia et al, 1991;Frorastiere et al, 1993;Poplin et al, 1994). The combination of 5-fluorouracil (5-FU) and cisplatin (CDDP) has become a standard regimen, not only because of the clinical outcome but also because of the synergism between the two agents and their radiosensitising effects (Douple et al, 1980;Scanlon et al, 1986;Byfield, 1990).…”
mentioning
confidence: 99%
“…In our own study published in 1991, 20% received a histologically complete response, and in this group all patients were long-term survivors. In all studies so far reported, improved survival is observed for patients who are pathologically complete responders (40)(41)(42)(43)(44)(45)(46)(47). A recently reported abstract of a Medical Research Council trial of chemotherapy before surgery versus surgery alone shows a statistically signi cant improvement in survival (48).…”
Section: Randomized Trialsmentioning
confidence: 99%
“…The swallowing function is often well restituted for responding patients and for those with remaining tumors surgical salvage is still possible. Several studies with preoperative chemoradiation have shown that a pathologically complete remission is predictive of those who will be long-term survivors (40)(41)(42)(43)(44)(45)(46)(47). This also stresses the need for a surgical resection.…”
Section: Non-surgical Treatmentmentioning
confidence: 99%
“…The use of pre-operative chemoradiotherapy in esophageal cancer was first used in 2 phase Ⅱ studies based in the United States [6,7] . The Southwestern Oncology Group trial accrued 113 patients treated with pre-operative chemoradiotherapy using concurrent cisplatin, fluorouracil and 30 Gy.…”
Section: Pre-operative Chemoradiotherapymentioning
confidence: 99%